IMPACT OF CLIMATE CHANGE PERCEPTIONS ON THE LIVELIHOOD OF SHEEP AND GOAT FARMERS IN OSUN STATE, NIGERIA - Abegunde, T O; Adedoyin, C A; Popoola, M A (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2017)
This study was conducted in the three Senatorial districts of Osun State with four Local Government Areas (LGAs) randomly selected within each Senatorial district to give a total of 12 LGAs with the objective of studying the perception of small ruminant farmers about climate change and its impact on their livelihood. 120 structured questionnaires were used through a multi-stage sampling technique. Result presentation and analysis were by percentages, frequency tables, Chi-square test and Kendall’s coefficient of concordance. Findings revealed that majority (57.3%) of the respondents were within the age range of 45-64 years. About 52.1% of the respondents were males, while 47.9% were females. Most (86.5%) of respondents were married and 4.2% were single. 10.4% had no formal education, while 89.6% had various levels of formal education. Highest flock sizes of between 10-19 were owned by about 44.8% of respondents. Lower years (1-10) of farming experience were indicated by more (65.6%) of the respondents.  50% of respondents strongly believed that rainfall patterns has been unpredictable recently while 62.5 % strongly believed that climate change has caused a reduction in the total number of small ruminants reared. The Kendall’s coefficient of concordance (W) was 0.64 with a calculated chi value of 31.41 implying that farmers did apply the same standard in ranking the statements related to their perceptions on climate change and agreed that small ruminants are affected by changes in weather condition It was concluded that small ruminant farmers in Osun State are knowledgeable about climate change and its impact on their livelihood and further recommended that this should be considered in policy formulation on adaptation of livestock production systems to climate change.